Single-replication BM2SR vaccine provides sterilizing immunity and cross-lineage influenza B virus protection in mice. Issue 32 (26th July 2019) - Moser, Michael J.; Hatta, Yasuko; Gabaglia, Claudia; Sanchez, Adriana; Dias, Peter; Sarawar, Sally; Kawaoka, Yoshihiro; Hatta, Masato; Neumann, Gabriele; Bilsel, Pamuk
Highlights: BM2SR is a novelBM2 -deleteds ingle-r eplication live influenza vaccine. Single replication BM2SR infects cells but does not produce next generation of virus. BM2SR elicits humoral, mucosal and cellular immune responses. BM2SR provides both homologous and heterologous protection against influenza B virus. Abstract: Both influenza A and B viruses cause outbreaks of seasonal influenza resulting in significant morbidity and mortality. There are two antigenically distinct lineages of influenza B virus, Yamagata lineage (YL) and Victoria lineage (VL). Since both B lineages have been co-circulating for years, more than 70% of influenza vaccines currently manufactured are quadrivalent consisting of influenza A (H1N1), influenza A (H3N2), influenza B (YL) and influenza B (VL) antigens. Although quadrivalent influenza vaccines tend to elevate immunity to both influenza B lineages, estimated overall vaccine efficacy against influenza B is still only around 42%. Thus, a more effective influenza B vaccine is needed. To meet this need, we generated BM2-deficient, single-replication (BM2SR) influenza B vaccine viruses that encode surface antigens from influenza B/Wisconsin/01/2010 (B/WI01, YL) and B/Brisbane/60/2008 (B/Bris60, VL) viruses. The BM2SR-WI01 and BM2SR-Bris60 vaccine viruses are replication-deficient in vitro and in vivo, and can only replicate in a cell line that expresses the complementing BM2 protein. Both BM2SR viruses were non-pathogenic to mice, and vaccinated animals showed elevated mucosal and serum antibody responses to both Yamagata and Victoria lineages in addition to cellular responses. Serum antibody responses included lineage-specific hemagglutinin inhibition antibody (HAI) responses as well as responses to the stem region of the hemagglutinin (HA). BM2SR vaccine viruses provided apparent sterilizing immunity to mice against intra- and inter-lineage drifted B virus challenge. The data presented here support the feasibility of BM2SR as a platform for next-generation trivalent influenza vaccine development.